Investigating student roles in online student-centered learning - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2007)
In this study we used the technique of Social Network Analysis (SNA) to investigate the roles students take on in an online student-centered learning environment, and more specifically in an online Computer Aided Language Learning (CALL) course. SNA is the mapping and measuring of relationships and flows between people, groups, organizations, computers or other information/knowledge processing entities (Krebs, 2004). We studied the interactions and communications of the students in the discussion boards of the language course and carried out Equivalence Analysis. Equivalence of the network members shows when two actors have similar patterns of relations. In other words, students with similar communication behaviors are grouped together. Being able to define, theorize about, and analyze data in terms of equivalence is important because we want to be able to make generalizations about social behaviour and social structure (Hanneman, 2001). Two nodes are said to be structurally equivalent if they have identical ties with themselves, each other and all other vertices. The aim of equivalence is to classify actors with similar roles into role groups by embedding the actors in a certain role space, identifying clusters of students and then carrying out subsequent cluster analysis to identify their roles.
Keywords: Social Network Analysis; Equivalence; Student Roles; Student-Centered Learning; Topic Relation Analysis; e-Learning; Computer Aided Learning